Effects of media campaign videos on stigma and attitudes towards treatment seeking for alcohol use disorder: a randomized controlled study - Sara Wallhed Finn; Anna Mejldal; Ruben Baskaran; Anette Søgaard Nielsen (BMC Public Health, 2023)
Abstract Background Alcohol Use Disorder (AUD) is one of the most stigmatized diagnosis, and stigma imposes a major barrier to treatment seeking. There is a need to develop interventions that can reduce stigma and increase treatment seeking. Little is known about the effects of video materials. The aim of this study was to investigate effects of different videos. The primary outcome was public stigma, and secondary outcomes were: self-stigma, and motivation to change own alcohol use; talking to someone else about their alcohol use; seeking information about AUD treatment or seeking AUD treatment. Methods This is a three-armed double blind randomized controlled study. The study included 655 Danish adults. Data was collected at a study webpage, and the survey could be completed anywhere with Internet access. After informed consent and completing baseline measures, participants were randomized, 1:1:1 ratio, to a video (video 1 n = 228; video 2 n = 198; video 3 n = 229). Video 1 and 2 have been used in a national mass media campaign and video 3 was recorded for use in the present study. Immediately after exposure, follow-up measures were completed. Outcomes were analyzed with mixed effects linear regression. Results In total n = 616 completed follow-up (video 1 n = 215; video 2 n = 192; video 3 n = 209). Randomization to video 1 and 3 decreased public stigma measured with “Difference, Disdain & Blame Scales”, while video 2 increased stigma. Video 2 compared to 1: 2.262 (95% CI 1.155; 3.369) p < 0.001. Video 3 compared to 1: -0.082 (95% CI -1.170; 1.006) p = 0.882. Video 3 compared to 2: -2.344 (95% CI -3.455; -1.233) p = 0.882. All videos reduced motivation to change own alcohol use. Participants with hazardous alcohol use, were more sensitive to the different videos, compared to low-risk alcohol use. Video 2 decreased motivation to seek information about treatment. No effects were seen on motivation to seek treatment, motivation to talk to someone else or self-stigma. Conclusions Videos can have an immediate effect on level of public stigma. Other types of interventions are needed to increase motivation and reduce self-stigma. To avoid adverse effects in future interventions, the use of theoretical frameworks and stakeholder involvement is emphasized.